2019
DOI: 10.1093/gji/ggz163
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and predicting corrections for empirical thermospheric models

Abstract: Quantifying spatial and temporal changes in thermospheric neutral density is important for various applications such as precise orbit determination, estimating mission lifetime and reentry prediction of Earth orbiting objects. It is also crucial for analysis of possible collisions between active satellite missions and space debris. Empirical models are frequently applied to estimate neutral densities at the position of satellites. But their accuracy is severely constrained by model simplifications and the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…1 ) shows the standardized solar index along-side of PC1. This confirms the previous results of e.g., Forootan et al 32 who reported that empirical models do not reflect recent neutral mass density changes caused by solar activity. The first mode of daily TND differences Fig.…”
Section: Resultssupporting
confidence: 92%
“…1 ) shows the standardized solar index along-side of PC1. This confirms the previous results of e.g., Forootan et al 32 who reported that empirical models do not reflect recent neutral mass density changes caused by solar activity. The first mode of daily TND differences Fig.…”
Section: Resultssupporting
confidence: 92%
“…These models consist of multilayer neurons that make a connection between inputs and outputs. This means that the output of each layer is a function of weight and bias of the existing neurons that pass through an activation function, and they are transmitted to the next layer until they end up at the last layer [25]. Therefore, an ANN can be considered a mapping function that projects the parameter of the input layer to the corresponding objective values in the output layer.…”
Section: Methods Extremely Learning Machine (Elm)mentioning
confidence: 99%
“…In this study, six radiosonde stations are considered, whose locations can be seen in Figure 5. For evaluating the results, the RMSE, Correlation Coefficients ( ), Mean Absolute Error (MAE), and Refined Willmott Index (RWI) statistical values are used, which can be calculated, respectively, as [4,25,48]:…”
Section: Region Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A logical step to make the best use of along-track TND observations and available models can be realised through the mathematical merging frameworks that build a connection between them. For example, (1) correction fields are applied as a ratio of TNDs from LEO satellites and those of models (Doornbos et al, 2005(Doornbos et al, , 2008Pérez et al, 2014;Shi et al, 2015;Ruan et al, 2018;Forootan et al, 2019;Weng et al, 2017). However, this method can only be used for reanalyzing and now-casting the thermosphere, and the reliability of these ratio fields, derived by a limited number of satellite tracks, might be treated with caution.…”
Section: Introductionmentioning
confidence: 99%